Understanding Students' Academic Resilience in Facing Skills Competency Test Anxiety Using the Draw and Tell Method - Jubaidah, Jubaidah; Irawan, Andi Wahyu (Indonesian Journal of Counseling and Development, 2025)
The Vocational School Competency Test (UKK) is an important final stage for students, but it often causes anxiety that affects their academic and psychological readiness. High pressure to pass UKK can lead to decreased confidence and stress among students. This study aims to understand the experiences of grade XII vocational school students in dealing with anxiety ahead of UKK and to explore the role of resilience in managing this anxiety. The subjects of the study were three grade XII vocational school students from different majors who were selected based on the criteria of experiencing anxiety related to UKK and having resilience characteristics. The approach used is qualitative with a double exploration case study design. Data was collected through in-depth interviews and draw and tell methods, then analyzed thematically. The results showed that students' anxiety was triggered by internal factors (e.g., self-doubt, technical unpreparedness) and external factors (parental pressure, negative stories from seniors, worries about examiners). Anxiety has a noticeable impact on students' daily activities, such as difficulty concentrating and enjoying free time. Resilience emerges as a protective factor through a variety of adaptive strategies, including practice and repetition of material, independent learning, positive affirmations, self-talk, and social support from peers and teachers. The draw and tell method effectively depicts a symbolic shift in students' emotions, from pre-exam anxiety to post-exam relief. These findings emphasize the importance of emotional support and mental guidance for vocational school students in dealing with UKK.